Sugar cane - Fauconnier, R. (Technical Centre for Agricultural and Rural Cooperation, 1993)
This booklet describes sugar cane cultivation in detail in a variety of agricultural systems and zones, from small plantations to large estates. Supplemented with numerous tables, the text provides readers with extensive information, from physiology and cropping cycles, practical growing techniques, planting, fertilisation and irrigation, to harvesting and processing.